Partisipasi Tenaga Kerja Perempuan dalam Meningkatkan Pendapatan Keluarga - Dewi, Putu Martini (Jurnal Ekonomi Kuantitatif Terapan; 2012: Vol. 5, No. 2, Agustus 2012 (pp. 79-150), 2012)
Women in a household beside as a wife, she also acts as a family manager. Unemployed spouse, low income, high number of family members, and spare time, are some of the reasons for women to involve in workfield. This paper employed the OLS method to investigate the impact of age, work hours, educational level, and number of children toward family income. The OLS estimates that all variables are significant to determine the family income. Age variable was indicate negative sign meanwhile the others are positive.
Keywords: women labor , family income , OLS